Ecology, climate change and control strategies for aspergillus flavus colonisation and aflatoxin contamination of pistachio nuts. - Baazeem, Alaa Abdulaziz (Cranfield University, 2017)
Pistachio nuts (Pistacia vera L.) have become one of the most important products in the economy of many countries including the USA, Iran, Syria, Greece, Turkey, China, EU and the Middle East. Pistachio nuts are very commonly colonized by spoilage mycobiota especially aflatoxigenic species because they are very hygroscopic and can adsorb water. Aspergillus flavus can contaminate pistachio nuts with aflatoxins (AFs), especially aflatoxin B1 (AFB1) classified as a class 1a carcinogen. The objectives of this project were (a) to examined the mycobiota and the aflatoxin producing strains of Aspergillus section Flavi species in pistachio nuts originating from different countries and sourced in the Kingdom of Saudi Arabia (KSA), (b) investigated the effect of the interactions between temperature and water activity (aw) on the ecology and molecular ecology growth and AFB₁ production by Aspergillus flavus strains in vitro on pistachio nut-based media and in stored raw pistachio nuts (c) evaluate the effect of Climate Change (CC) interacting factors on growth and AFB1 production by strains of A.flavusand on relative genes expression of the aflD and aflR genes involved in the biosynthetic pathway for AFB₁ production, (d) examine whether acclimatisation to 1000 ppm CO₂ of A.flavus strains AB3 and AB10 for 5 generations affected growth and AFB₁ production; and (e) to examine the use of gaseous O₃ for the control of germination, A.flavus populations and AFB₁ contamination of stored pistachio nuts for up to 4 weeks. Pistachio samples were colonized by a range of Aspergillus and Penicillium species. In some samples, typically phyllosphere fungi such as yeasts, Mucor, Rhizopus, Alternaria, Epicoccum and Phoma species were isolated. 10 different species of A.flavus were isolated and molecularly identified. The relative toxigenic nature of strains was evaluated using selective media and HPLC and confirmed using molecular tools. Four strains were used in ecological studies and two (AB3, AB10) in other studies. The ecological studies showed that optimum growth of AB3 and AB10 strainswas at 0.98 or 0.95 aw and 30-35°C. The effect of the same factors on aflR gene expression of the two strains showed optimum condition at 30-35°C and 0.98 aw; with optimum conditions for AFB₁ production at 35°C and 0.98 aw for strain AB3. There was little difference between the effect of using a non-ionic (glycerol) or ionic (NaCl) to modify water stress in in vitro studies. The effect of interacting CC factors on growth of A.flavus colonisation was not significant. However, AFB₁ production was stimulated. With regards to aflD gene expression, at 35°C, the relative expression was higher in current CO₂ conditions (400 ppm) for both strains except that for strain AB3 the gene expression was higher at 1000 ppm CO2 at 0.95 aw. However, at 37°C, the expression was generally higher in the 1000 ppm CO₂ than with existing atmospheric CO₂ levels. The aflR gene expression was higher at 1000 ppm CO₂ at 37°C for both strains. AFB₁ production was higher at 35°C at the two CO₂ levels for both strains. At the same temperature, AFB1 production was significantly increased at 1000 ppm CO₂ and 0.98 aw. At 37°C, AFB₁ production was either decreased in strain AB3 or similar as in strain AB10 when exposed to 1000 ppm CO₂. This suggests that CC factors may have a differential effect depending on the interacting conditions of temperature (35 or 37°C) as in some cases for AFB₁. Acclimatisation influenced growth of one strain while there was no significant effect on another strain when colonising pistachio nuts. For AFB₁, the production was significantly stimulated after ten days colonisation after acclimatisation for one strain, while there was no significant increase for the other strain. This suggests that there may be intra-strain differences in effects of acclimatisation and this could influence mycotoxin contamination of such commodities as mixed population of contaminant fungi often occurs. Exposure of conidia to gaseous O₃ initially had lower germination percentages when compared to the controls at different aw levels. Complete inhibition of germinations was observed after 12 h treatment of 200 ppm O₃ at 0.98 aw. However, spore viability appeared to recover and the germination was increased after 24 h and reached 100% after 48 h. Growth rates of mycelial colonies were decreased with increasing of O₃ dose and colony extension was significantly inhibited by O₃ treatment at 0.98 aw. Variable effects on AFB1 production during exposure to O₃ treatment after in vitro exposure of colonies of A.flavus incubated for ten days at 30°C. The populations of A.flavus were significantly decreased by O₃ exposure; however, there was little difference between 50-200 ppm treatment levels. A reduction in AFB₁ was only observed in the 50 ppm O₃ × 0.98 aw treatment in stored pistachio nuts. The relationship between exposure concentration × time of exposure and prevailing aw level to determine the efficacy in terms of toxin control needs to be better understand.
Keywords: A. flavus; AFB₁; ecology; climate change; O₃; pistachio